A COMPARATIVE ANALYSIS OF THE APPLICATION OF CROSS CULTURAL PRACTICES MODEL BETWEEN PATIENTS SEEKING TREATMENT IN WESTERN MEDICINE AND TRADITIONAL ASIAN MEDICINE - Amir Lukman Bin Abd Rahman; Nur Afifah Diyanah Shaharudin; Amirah Athirah Amir Yazid; Anis Shahira Bazlan (Journal of Islamic, Social, Economics and Development, 2022)
The usage of Traditional Asian medicine has been acknowledged in complementing it with western modern medicine especially in Malaysia. Therefore, this study aimed to assess the views on the comparison of the application of cross-cultural practices model between patients seeking Western medicine and Traditional Asian medicine treatments among Malay, Chinese and Indian. A semi-structured interview was conducted among six patients receiving Western medical treatments and Traditional Asian medical treatments. Data from the interview were analysed through three types of practices from Lawrence’s (2004) model for crosscultural practices in comprehending the patients’ perspectives on both treatments. Results of the study showed that patients who had received treatments from Western medicine and Traditional Asian medicine agreed that both medications were effective in treating their illnesses. Moreover, the decisions to have chosen such treatments were influenced by their family members, friends’ recommendations, and visitations from the medical institutions. Factors such as the the prescription of medication, daily supplements and procedure of the treatment were the major causes in deciding the chosen treatment. Given that different races in Malaysia gave positive feedbacks on both types of treatments, this suggests medical practitioners and authorities to boost their strategies in the incorporation of traditional and modern medicines as aligned with the Malaysia’s Traditional and Complementary Blueprint 2018-2022.